Turn around excellence insights from 120 cases - Khandwalla, Pradip N (New Delhi Response Books, 2001)
Turnarounds are amongst the most attractive and dazzling of corporate phenomena, associated with the revitalization of previously sick organizations. In this trailblazing book,the Author studies 120 recent examples of turnarounds and analyzes how each was
Keywords: Corporate turnarounds-Management